Из истории экономического развития Херсонеса-Херсона во второй половине I в. до н.э. – VI в. н.э. - Зубарь, В.М. (Боспорские исследования, 2009)
Based on the archaeological materials the author analyses in the article the main tendencies of economic development of Chersonesos-Kherson during the Roman and the late-ancient periods of the history of this centre. As a result, the author has concluded that in the 4th'-3rd cc. BC, production of goods, except for home consumption, took place mainly outside the city borders, in the nearest vicinity of C'hersonesos and on the Herakleian Peninsula. Situation changed from the 2nd c. BC.